Accountability Relations in Social Housing Programs : A comparative legal analysis of Brazilian and Chilean case studies - Vilmondes, Mariana (2022)
Institutional crises have been continuously embeded in weak accountability. In Latin America, human rights' violations catalyze the outcomes of such crises. In the aim of understanding the housing crisis, this research evidenced a vicious cycle in Brazil and Chile: despite the creation of massive social housing programs, the lack of adequate housing particularly affects the most-poor due to weak accountability. The comparison of legal accountability relations in the urban social housing ownership models Minha Casa, Minha Vida, from Brazil, and D.S. 49, D.S. 1, and D.S. 19, from Chile, revealed several of those inconsistencies, but also advised on concrete solutions to their accountability relations inspired by the rights-based approach. Policies fall short on the organization of responsibilities to duty-bearers, whose weak obligations to inform, justify or respond neutralize concrete chances of enforcing redress or grievance. In such a scenario, this research showed that the most-vulnerable remain hindered from accessing the minimum existencial and, particularly, adequate housing. The solution is obvious: the respect, protection and fulfillment of human rights must be used as means and goals of those or any other policies and institutional structures.